Similarities and differences of chemical compositions and physical and functional properties of adjuvant system 01 and army liposome formulation with QS21 - Alving, Carl R.; Rao, Mangala; Matyas, Gary R. (Frontiers in Immunology, 2023)
A vaccine adjuvant known as Adjuvant System 01 (AS01) consists of liposomes containing monophosphoryl lipid A (MPLA) and a tree saponin known as QS21. Two vaccines containing AS01 as the adjuvant have been licensed, including a malaria vaccine (Mosquirx®) approved by World Health Organization and European Medicines Agency for use in sub-Saharan Africa, and a shingles vaccine (Shingrix®) approved by the U.S. Food and Drug Administration. The success of the AS01 vaccine adjuvant has led to the development of another liposomal vaccine adjuvant, referred to as Army Liposome Formulation with QS21 (ALFQ). Like AS01, ALFQ consists of liposomes containing MPLA and QS21 as adjuvant constituents, and the polar headgroups of the liposomes of AS01 and ALFQ are similar. Based on the existence of two liposomal vaccine adjuvants containing the same adjuvant constituents, we compare here AS01 with ALFQ with respect to their similar and different liposomal chemical structures and physical characteristics with a goal of projecting some of the likely mechanisms of safety, side effects, and mechanisms of adjuvanticity. We hypothesize that some of the side effects exhibited in humans after injection of liposome-based vaccines might be caused by free fatty acid and lysophospholipid released by enzymatic attack of liposomal phospholipid by phospholipase A2 at the injection site or systemically after injection.